If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -6 = 10z + 6 Reorder the terms: -6 + 2z = 10z + 6 Reorder the terms: -6 + 2z = 6 + 10z Solving -6 + 2z = 6 + 10z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-10z' to each side of the equation. -6 + 2z + -10z = 6 + 10z + -10z Combine like terms: 2z + -10z = -8z -6 + -8z = 6 + 10z + -10z Combine like terms: 10z + -10z = 0 -6 + -8z = 6 + 0 -6 + -8z = 6 Add '6' to each side of the equation. -6 + 6 + -8z = 6 + 6 Combine like terms: -6 + 6 = 0 0 + -8z = 6 + 6 -8z = 6 + 6 Combine like terms: 6 + 6 = 12 -8z = 12 Divide each side by '-8'. z = -1.5 Simplifying z = -1.5
| 2=-2(n-7) | | (3(42.5)+x+10)+(42.5+x)=180 | | 6y^2-2y-3=0 | | 5h+9+7h= | | 2(4e)=10 | | 13=3u-14 | | ln(x+3)=0.8 | | 0.666666666667x+6=0.5x+0.25x | | 2(4e)=90 | | 5+.1q=20-.2Q | | (3(42.5)+y+10)+(42.5+y)=180 | | 12+4(z-3)=-3z+6 | | 5w+11=96 | | 2x+2y+1+3x+1=180 | | (A+p)(a^2-ap+p^2)= | | 2(4e)=20 | | 24=4y-16 | | 2x+8+74+5x= | | 2(x+7)+3x=-4 | | 20.6+2.7x=-8.2x | | 15a*2+26a*2+a*2= | | 4x^2-29x=-3x^2-4x-12 | | 0.75=x+1.75 | | (3x+y+10)+(x+y)=180 | | (8y+7)(8y+27)=0 | | 4(3x-2)=6(4x-2) | | 27=5+9(x+8) | | 7+2(b-3)=-9 | | 2x^2-6x-8=8 | | x(5x+3)=2x^2-5x+3 | | 62-x=281 | | -7-9x=-61g |